THE SIGNIFICANCE OF MINIMAL RESIDUAL DISEASE IN ACUTE LYMPHOBLASTIC LEUKAEMIA: A SINGLE CENTRE STUDY - Muhsin, Abdulrahman A.; Atrushi , Akrem M.; Al-Doski, Adnan A. (Science Journal of University of Zakho, 2024)
In Acute lymphoblastic Leukemia (ALL) assessment of molecular response to treatment, assessing minimal residual disease (MRD) is a major independent predictor of treatment outcome. Consequently, MRD is implemented in all ALL-treatment protocols to fill up or to redefine stratification of multifactorial risk with optional intensity of customized treatment.Aim: to specify the significance of MRD in the assessment of remission in children with ALL with results discordant between morphology and flow cytometry at the end of induction phase of therapy.Materials and Methods: A descriptive cross-sectional study was conducted at Jin Oncology Center from March 2019 through November 2023. Data were taken out of the records of 58 patients who had ALL less than 16 years old. All patients were less than 16 years old and treated by ukall. They were diagnosed using peripheral blood morphology, bone marrow study and/or flow cytometry when lymphoblasts in peripheral blood or bone marrow aspirate are ≥20% and was confirmed by flow cytometry. On 29th day of induction therapy, bone marrow was examined for morphology and flow cytometry. The presence or absence of MRD was determined, and CD19, CD10 and tdt were tested. By morphologic assessment they were divided patients into: Category 1, C1 (20% blasts). Statistical analysis was made using SPSS version 25. P value of less than 0.05 was considered significant.Results: The study involved 58 patients who had ALL. with a median age of 6.5 years, male to females ratio of 1.76:1, mean platelet count of 96.6 x 10⁹/L ,mean hemoglobin of 8.6 g/dL, mean leucocyte count of 74.3 x 10⁹/L), 48 cases (82.7%) of B-cell lineage and 10 cases (17.3%) of T-cell lineage, 94.6% of the B-cell cases were of the common B-ALL and the rest Pro-BALL type, 54.6% of the T-cell ALL was cortical T-ALL  and 44.4% Early T-cell ALL.  They were tested for MRD by morphology and flow cytometry on day 29. By morphology, 46 patients had remission but by flow only 24 cases. Seventeen cases had residual blasts >5%. In 19 cases there was a discrepancy between the results of morphology and flow. Twenty-five cases (52.08% of B-cell cases) were positive for MRD by flow results. Eight of the ten cases of T-ALL (80%), were positive for MRD by flow cytometry. Among 48 cases of B-ALL, 36 were in C1 category (morphologically in remission), 11 cases were in C2 category and one case in the C3 category. Of cases in C1 category, 17 were MRD +ve and 19 were MRD –ve by flow cytometry. In the C2 category, only 2 out of the 11 cases (18.18%) had discordant results between morphology and flow results. The correlation between morphology and flow results was 100% in the C3 category.Conclusion: MRD should not be the surrogate of morphology but to be used in conjunction in order to give us a more accurate representation of status of remission.
Keywords: Leukemia; minimal residual; flowcytometry; remission